2015
DOI: 10.1136/annrheumdis-2015-eular.1472
|View full text |Cite
|
Sign up to set email alerts
|

AB0531 The Efficacy and Tolerability of H.P. Acthar® Gel (Repository Corticotropin Injection) for the Treatment of Systemic Lupus Erythematosus

Abstract: BackgroundActhar Gel has been approved for use in multiple rheumatic/inflammatory conditions since the early 1950s, yet the current literature remains sparse on its real-world clinical efficacy and safety. In addition to the well-established steroid-dependent effects of Acthar Gel, research suggests it has direct steroid-independent immunomodulatory effects in a variety of tissues due to its ability to bind to multiple melanocortin receptors. Clinical reports on the real-world efficacy and safety of Acthar Gel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…Recent progress in understanding the effects of RCI in modulating immune responses has led to increased interest in RCI as a therapeutic choice [2]. Clinical trials and retrospective case series have found RCI to be effective for reducing disease activity and signs/symptoms as well as improving functional status in patients with RA, PsA, DM/PM, and SLE [3][4][5][6][7][8][9][10][11][12]. Claims data studies that examined medical resource use (MRU) relating to rheumatologic disorders reported that RCI treatment was associated with reduced health care utilization [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Recent progress in understanding the effects of RCI in modulating immune responses has led to increased interest in RCI as a therapeutic choice [2]. Clinical trials and retrospective case series have found RCI to be effective for reducing disease activity and signs/symptoms as well as improving functional status in patients with RA, PsA, DM/PM, and SLE [3][4][5][6][7][8][9][10][11][12]. Claims data studies that examined medical resource use (MRU) relating to rheumatologic disorders reported that RCI treatment was associated with reduced health care utilization [13,14].…”
Section: Introductionmentioning
confidence: 99%